mGlu7 receptor modulation of synaptic transmission and short-term plasticity at the CA1 and dentate gyrus areas of the hippocampus - Pires, Johny Helder da Silva Dias (2014)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra.